Orçamento para resultados: experiências para subsidiar Sergipe - Nascimento, Antonio Marcos Almeida (2021)
The Budget for Results is part of the New Public Management. Although it does not consist of a standard model, it is possible to identify a set of principles and characteristics common to this new form of management: the change of focus of the process (characteristic of the bureaucratic model) to the results expected by the client/citizen; greater use of contractualization; use of private sector instruments, such as strategic planning and quality management; and, search for leaner and more decentralized structures. Management for Results, as the New Public Management has come to be called, has the function of facilitating public organizations the effective and integrated direction of their process of creating public value, in order to optimize it, ensuring maximum effectiveness, efficiency and performance effectiveness, in addition to achieving government objectives and improving its institutions. In this perspective, the objective is to analyze practices of the government of Sergipe – Results Center, Participatory and Territorialized Planning, Quality Index of Budget Management – as experiences that will help in the implementation of the Budget for Results. To understand this model, a comparative study was carried out based on the literature that deals with the theme in Brazil (Federal Government and states of Minas Gerais and Ceará) and in other countries, such as England and the United States, where it all started. This work is justified due to the scarcity of analyzes on the effectiveness of the Budget for Results in relation to the performance of governments and, also, for presenting a management model that can be followed by other units of the federation, such as Sergipe.